2014
DOI: 10.1309/ajcptgjopxuw6rvo
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Atypical Hyperplasia in the Endometrium of Patients With Epithelial Ovarian Cancer

Abstract: Apart from synchronous endometrial carcinoma, endometrial premalignancies should be taken into account when determining optimal treatment for women diagnosed with EOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Up to 42% of women in whom endometrial sampling reveals atypical endometrial hyperplasia are found to have simultaneous endometrial cancer in hysterectomy specimens [15] consistent with the idea that endometrioid endometrial carcinoma evolves via endometrial hyperplasia [16]. Interestingly, some 50% of patients with endometrioid ovarian carcinoma, too, display concurrent atypical endometrial hyperplasia [17], the significance of which remains to be clarified: does endometrial hyperplasia represent an early step of synchronous endometrial tumorigenesis or have relevance for ovarian cancer development as well, given that endometrial epithelial cells are considered to be the origins of endometrioid and clear cell carcinomas of the ovary [18]?…”
Section: Introductionsupporting
confidence: 56%
“…Up to 42% of women in whom endometrial sampling reveals atypical endometrial hyperplasia are found to have simultaneous endometrial cancer in hysterectomy specimens [15] consistent with the idea that endometrioid endometrial carcinoma evolves via endometrial hyperplasia [16]. Interestingly, some 50% of patients with endometrioid ovarian carcinoma, too, display concurrent atypical endometrial hyperplasia [17], the significance of which remains to be clarified: does endometrial hyperplasia represent an early step of synchronous endometrial tumorigenesis or have relevance for ovarian cancer development as well, given that endometrial epithelial cells are considered to be the origins of endometrioid and clear cell carcinomas of the ovary [18]?…”
Section: Introductionsupporting
confidence: 56%
“…They concluded that this condition is more frequent in clear cell carcinomas than epitelial ovarian carcinomas. Mingels et al [21] analized histological samples from 186 pacients diagnosed with epithelial ovarian cancer and discovered high prevalence of atypical hyperplasia in the endometrium, and reports in 81 pacients(44%) endometrial lesion who was premalignant in 58(31%) pacients and malignant in 6(3%), primary endometrial carcinoma. Same authors reported a higer body mass index (BMI) in pacients with atypical endometrial hyperplasia in comparation in pacients with normal endometrium, and performed genetical tests who described BRCA mutation carriers in both groups.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the 15 patients in Morrison (26) examined tubes from 200 randomly selected patients with endometrial carcinomas (100 were entirely embedded and 100 were routinely sampled without fimbrial sections) and did not find STIC; however, lack of uniform fimbrial sampling is a limitation of this study. Interestingly, Mingels et al (27) reviewed the endometrium in 136 women with serous ovarian carcinomas and found atypical hyperplasia in 32 (24%) and endometrioid carcinoma in 2 (1.5%). Although our findings are not statistically significant, and more data are needed, together the findings suggest that, although infrequent, there may be an association between STIC and nonserous adenocarcinoma of the endometrium that remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%